PENGGUNAAN ALAT PERAGA DENGAN PEMBELAJARAN LANGSUNG DALAM MENINGKATKAN MOTIVASI MENGAJAR GURU DI SD NEGERI 010 PAGARAN TAPAH DARUSSALAM KABUPATEN ROKAN HULU - Sri Rahayu (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research was motivated by the low motivation of teaching teachers in SD Negeri 010 Pagaran Tapah Darussalam. Thisstudy aims to improve teacher teaching motivation through the use of teaching aids with direct learning. The subjects of thisstudy were all teachers of the SD Negeri 010 Pagaran Tapah Darussalam totaling 10 people, the academic year 2018-2019.The form of research is school action research. The instrument of this study consisted of performance instruments and datacollection instruments in the form of observation sheets for school principal activities and teacher motivation. Based on theresults of the study it is known that the activity aspect of the principal as a facilitator gets achievement with a score of 25 orwith a percentage of 63 of all aspects of the assessment or 63% of all activities achieved. Then in the second cycle the scoreobtained was 38 or with an achievement percentage of 95% of all aspects achieved. The aspect of teacher activity as aparticipator in this study is that in the first cycle the scores obtained from the direction of the headmaster get a score of 44 oran achievement percentage of 55%. Then in cycle II the participation rate was 78% higher than the first cycle and with animplementation score of 62. Aspects of teacher teaching motivation during the implementation of the direction from cycle I tocycle II, the motivation of teachers to use props tended to increase. Where if in the first cycle obtained an achievementpercentage of 68% with a good category, then the second cycle obtained a percentage of 89% or with a very good category.